PELAKSANAAN KEWENANGAN UPT PENGAWAS DAN SERTIFIKASI BENIH PROVINSI NUSA TENGGARA TIMUR TERHADAP BENIH BINA DAN HORTIKULTURA DITINJAU DARI PERATURAN MENTERI NOMOR 12 TAHUN 2018 TENTANG PRODUKSI, SERTIFIKASI DAN PEREDARAN BENIH BINA TANAMAN - Saleh, Saptian Haryanto Muhammad; Tupen, Rafael R; Ratu Udju, Hernimus (Petitum Law Journal, 2023)
Thus, the seed problem in East Nusa Tenggara Province is not only related to the ability to provide quality seeds in sufficient quantities, but also related to the problem of falsification of seeds in circulation to meet the needs of seeds for farmers. This research uses juridical-empirical research methods, namely research whose data is directly obtained from the research location of the respondent (resource person). The results of this study indicate that: (1) The implementation of the authority of the technical implementation unit of supervision and Certification of Bina Seeds in East Nusa Tenggara Province is not so good because there are still in certain districts / cities in East Nusa Tenggara there is circulation and marketing of Bina Seeds and Certified Horticulture carried out by the Technical Implementation Unit based on legal legality. (2) Factors that inhibit the Implementation of the Authority of the Technical Implementation Unit of Supervision and Certification of Seeds of East Nusa Tenggara Province on Bina and Horticultural Seeds are internal factors in the form of rules, human resources, technology / infrastructure and lack of supervision and external factors in the form of socio-cultural conditions, (3) Efforts to Protect and Empower Farmers in East Nusa Tenggara so far have not been supported by comprehensive, systemic, and holistic legislation, so as to provide less assurance of legal certainty and justice for Farmers and Business Actors in the field of Agriculture. The existing laws are still partial and do not regulate protection and empowerment efforts in a clear, firm, and complete manner. Seed Distribution in East Nusa Tenggara Province has not been in accordance with the applicable rules, namely Law Number 13 Year 2010 on Horticulture in Chapter XII Article 117 on Supervision, Supervision is carried out in order to ensure the quality of facilities and / or horticultural products in accordance with established quality standards and to overcome various negative impacts that are detrimental to the wider community.Supervision as referred to in paragraph (1) is carried out in stages by the Government, provincial government, and district / city government in accordance with their authority by involving community participation.